Peranan Bank Penerbit Bank Garansi sebagai Penjamin Pelaksanaan Pekerjaan Konstruksi Pembangunan Rumah Susun dalam Meningkatkan Perlindungan Hak Konsumen - Johannes Ibrahim; Rahel Octora; Yohanes Hermanto Sirait (Faculty of Law, Maranatha Christian University, 2016)
Bank guarantee is a promise from a bank that the liabilities of a debtor will be met in the event that you fail to fulfill your contractual obligations (event of default). Bank guarantee also known as surety agreement where third party, for owing, attach their self to fulfill owing’s obligation when those owing unable to do. This article examine how does an agreement between bank guarantee and developer on project of flat construction in the case of event of default. This article also examine whether bank guarantee agreement able to ensure legal certainty to developer and protect consumer right. Last, this article will see how does bank guarantee can protect and fulfill the rights of consumers.